Impact of oral anticoagulation on proximal femur fractures treated within 24 h – A retrospective chart review. Issue 11 (November 2019) - Schuetze, K.; Eickhoff, A.; Dehner, C.; Gebhard, F.; Richter, P.H.
Highlights: First study that investigates patients on anticoagulant medication with proximal femur fractures that were operated within 24 h. Patients taking ASS, TIA or VKA showed no higher rates of blood transfusions or Hb-differences. Patients taking DOAC had a 3.4-fold risk for intraoperative blood transfusion. Early surgical care of proximal femur fractures is safe even in patients with anticoagulant medication. Abstract: Background: About one third of all patients with proximal femur fractures take oral anticoagulation like aspirin (ASS), direct platelet aggregation inhibitors like Clopidogrel and Ticagrelor (PAI), vitamin-K-antagonists like Warfarin (VKA) and direct oral anticoagulants like Rivaroxaban, Dabigatran and Apixaban (DOAC). The management and timing of fracture stabilization of these patients is a rising challenge in orthopedic trauma. Our objective was to determine the effect of oral anticoagulation on patients with proximal femur fractures, which received a proximal femur nail antirotation (PFNA) within 24 h after trauma. Material and methods: A retrospective chart review of 327 patients (mean age 80 ± 13 years; 223 women and 104 men) with sub- or intertrochanteric fractures between January 2013 and December 2017 was performed. All patients underwent surgery in the first 24 h after admission. Solely patients without or with only one type of oral anticoagulation were included. There were 74 patients with ASS, 30 with PAI, 52 with DOAC and 25 with VKA medication. All patients taking VKA received high dose Vitamin K or coagulation factors to normalize INR prior to surgery. Primary outcome measures were transfusion rate and pre- and postoperative hemoglobin (Hb) difference. Secondary outcome measures were mortality and complications like infection, hematoma and acute cardiovascular events. Results: Patients undergoing treatment with DOAC had a 3.4-fold increased risk for intraoperative blood transfusion. The risk for blood transfusion for patients taking ASS, PAI or VKA did no differ from the control group. Patients without an intraoperative blood transfusion on oral anticoagulation showed no increase in pre- and postoperative Hb-difference compared with controls. Anticoagulation showed no significant effect on complication rates and mortality in patients operated within the first 24 h. Conclusion: Early surgical care of proximal femur fractures is safe even in patients with anticoagulant medication. All patients should be preoperatively prepared for possibly intraoperative transfusion, especially patients on DOAC.